2014
DOI: 10.1093/jnci/dju169
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Integrin αvβ6 in Breast Cancer

Abstract: BackgroundIntegrin αvβ6 promotes migration, invasion, and survival of cancer cells; however, the relevance and role of αvβ6 has yet to be elucidated in breast cancer.MethodsProtein expression of integrin subunit beta6 (β6) was measured in breast cancers by immunohistochemistry (n > 2000) and ITGB6 mRNA expression measured in the Molecular Taxonomy of Breast Cancer International Consortium dataset. Overall survival was assessed using Kaplan Meier curves, and bioinformatics statistical analyses were performed (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(142 citation statements)
references
References 34 publications
10
122
0
Order By: Relevance
“…found that approximately 15–16% of the London and Nottingham cohort had detectable α v β 6 integrin expression 14. Our ROC analysis of the KMIO‐CS of α v β 6 integrin protein versus ITGB6 transcript levels had yielded a good concordance (AUC = 0.83; P  < 0.0001) with 93% specificity.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…found that approximately 15–16% of the London and Nottingham cohort had detectable α v β 6 integrin expression 14. Our ROC analysis of the KMIO‐CS of α v β 6 integrin protein versus ITGB6 transcript levels had yielded a good concordance (AUC = 0.83; P  < 0.0001) with 93% specificity.…”
Section: Resultsmentioning
confidence: 61%
“…Scoring of integrin α v β 6 was done as reported by Moore et al. 14 in their supplementary data. TMA cores with less than 100 invasive tumor cells were considered inadequate for interpretation and were dropped from further scoring.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrin beta 6 mRNA expression, which is 7.7-fold higher in this subpopulation, has been shown as an independent predictor of survival, and high expression is associated with distant metastasis and poor survival in breast cancer (58) as well as in colon cancer where it also appears to confer chemoresistance (59). A number of upregulated secreted factors with roles in cancer metastasis, angiogenesis, and hypoxia (e.g., TGFB1, LOXL4, WNT4) add to the interpretation that these cells communicate actively with their surrounding and may have a more significant role in the interaction with the TME than their CD184 hi counterparts.…”
Section: Discussionmentioning
confidence: 96%